Social barriers influence inflammatory bowel disease (IBD) outcomes and disproportionally affect Hispanics and non-Hispanic Blacks with IBD. (March 2022) - Damas, Oriana M.; Kuftinec, Gabriela; Khakoo, Nidah S.; Morillo, Diana; Quintero, Maria A.; Leavitt, James; Lopez, Joanna; Kerman, David H.; Abreu, Maria T.; Deshpande, Amar R.; Schwartz, Seth J.; Palacio, Ana
Background: The impact of social determinants of health in inflammatory bowel disease (IBD) remains understudied. We evaluated the impact of social barriers on IBD outcomes within a diverse cohort of patients. Methods: We performed a cross-sectional study on adult IBD patients and assessed known social determinants of health. We calculated the total prevalence of these barriers in the sample as a whole and within each ethnic group. We summed the number of barriers present for each individual to create a cumulative social barrier score (SBS), and we evaluated the relationship of each barrier and of the cumulative SBS with IBD outcomes, including disease activity and depressive symptoms. Results: A total of 316 patients were included in the study. Disparities in the prevalence of social barriers emerged by ethnicity: non-Hispanic Blacks reported the greatest number of social barriers, followed by Hispanic patients. Prevalent social barriers included financial strains (38.4%), (such as food insecurity), medical care delays ( 30%), and low educational attainment (26.8%). Social barriers associated with poor IBD outcomes included low educational attainment, poor health literacy, and financial insecurity. High SBS was associated with greater depressive symptoms [odds ratio (OR) 1.94, 95% confidence interval (CI) 1.21–2.9, p = 0.001] and lower reported use of medications. Greater ulcerative colitis (UC) disease activity was observed in patients with greater SBS. No associations were identified between SBS and IBD surgeries, hospitalizations, or disease location. Conclusion: Our study identifies social barriers that may impact IBD care and are disproportionately higher in non-Hispanic Blacks and Hispanics in the United States. Future studies should focus on implementing interventions to reduce these barriers and improve delivery of care.